An english syllabus with emphasis on chemistry: a proposal for 10th graders of a public school in colombia (2009)
Abstract This article describes the process followed to design an English syllabus with emphasis on chemistry. It was focused on 10th grade students as they started a connection with a program named “Chemical Samples Analysis”. In that attempt, esp (English for Specific Purposes) and creative thinking theories were taken into account. A students’ questionnaire, teacher’s audio-taped interviews and a teacher researcher journal comprised data for the research. It was found that the English class needs to be reorganized by taking into account students’ needs and interest and by integrating the four language skills. This way the English language process can become more meaningful. Key words: English for specific purposes, creative thinking, chemistry, curriculum design Este artículo describe el proceso que se siguió al diseñar un plan de estudios de inglés con énfasis en química, el cual se enfocó en estudiantes de grado 10.º, quienes iniciaron una conexión con el programa “Análisis de muestras químicas”. Se tomaron en cuenta las teorías de inglés para propósitos específicos y pensamiento creativo. Para la recolección de datos se emplearon un cuestionario para los estudiantes, entrevistas grabadas a los docentes, cuestionarios para los estudiantes y un diario de campo de la docente investigadora. Se concluyó que la asignatura de inglés necesita reorganizarse teniendo en cuenta las necesidades e intereses de los estudiantes y mediante la integración de las cuatro habilidades del lenguaje. De esta manera el proceso de aprendizaje del inglés puede ser más significativo. Palabras clave: Inglés para propósitos específicos, pensamiento creativo, química, diseño curricular